PENGGUNAAN MODEL PEMBELAJARAN PREVIEW, QUESTIONS, READ, REFLECT, RECITE, REVIEW (PQ4R) UNTUK MENINGKATKANAKTIVITAS DAN HASIL BELAJAR BIOLOGI - Wondal, Rosita (Jurnal Pendidikan Dasar, 2016)
PQ4R is a model that used to help students understand the matter, because this learning model the students are asked to read the sub topics or the title of matterial that appropriate with the aim of learning. Result of learning is students competence to reach a level of learning experience in basic competence.This research is an action Research. The aim of research is increasing actvity and result biology learning on students grade VIII1 SMP Negeri 5 Kota Tidore Kepulauan on concept Human Breathing system. The subject of the research were 20 students. The result of research have shown the mean score of students’ learning Biology after using PQ4R Learning model (Preview, Questions, Read, Reflect, Recite, Review) firts cycle were as much as 8 students or 40 % than second cycle increase 16 student or as much as 80.00%. The result presentation of students observation activity in first cycle is 49.99% and the second cycle reached 74.99%. Using PQ4R Learning Model (Preview, Questions, Read, Reflect, Recite, Review, can increase activity and Biology study grade VIII1 SMP Negeri 5 Kota Tidore Kepulauan on concept Human Breathing System. Keyword : Learning ModelPreview, Questions, Read, Reflect, Recite, Review (PQ4R), result study. PQ4R merupakan model pembelajaran, dengan tujuan untuk meningkatkan daya paham dan daya ingat siswa kepada tentang materi yang mereka baca. Hasil belajar merupakan kemampuan siswa dalam memenuhi suatu tahapan pencapaian pengalaman belajar dalam kompetensi dasar.Penelitian ini merupakan penelitian tindakan kelas, dengan tujuan adalah untuk meningkatkan aktivitas dan hasil belajar biologi siswa kelas VIII1 SMP Negeri 5 Kota Tidore Kepulauan pada konsep sistem pernapasan pada manusia. Subjek penelitian berjumlah 20 siswa.Hasil penelitian yang diperoleh dari penelitian ini yaitu nilai rata hasil belajar Biologi siswa setelah diterapkan model pembelajaran PQ4R (Preview, Questions, Read, Reflect, Recite, Review) pada siklus I hasil belajar siswa yang tuntas sebanyak 8 orang (40%) sedangkan pada siklus II meningkat menjadi 16 siswa (80%). Presentase hasil pengamatan aktivitas siswa pada siklus I yaitu 49,99% dan siklus II meningkat mencapai 74,99%. Penerapan model pembelajaran PQ4R, dapat meningkatkan hasil belajar biologi di kelas VIII1 SMP Negeri 5 Kota Tidore Kepulauan pada konsep sistem pernapasan pada manusia. Kata Kunci: Model Pembelajaran Preview, Questions, Read, Reflect, Recite, Review (PQ4R), Hasil belajar.